Evaluation of analgesic, antipyretic, hypoglycemic and CNS depressant activity of 2-bromopopylamine hydrobromide, 3-bromopopyl ammonium bromide, ortho-amino aniline and benzimidazole-2-thiol in animal model - Md. Hamiduzzaman; Dey, Avijit; Mannan, Sultana Juhara; Rahman, S. M. Abdur (© 2014 Der Pharmacia Lettre, 2016)
Synthetic compounds are encompassing the major ther apeutic classes of drugs which resemblance to the n atural or existing therapeutically active compounds. Herewith four synthetic compounds i.e. 2-bromopropylamine hydrobromide, 3-bromopropyl ammonium bromide, ortho -amino aniline and benzimidazole-2-thiol were subje cted for analgesic, antipyretic, hypoglycemic and CNS de pressant activity in mice and rat model following s tandard protocol. Among the four supplied synthetic compoun ds, benzimidazole-2-thiol and 3-bromopropyl ammoniu m bromide at a dose of 50 mg/kg body wt revealed sign ificant analgesic activity with 37.85% and 42.85% i nhibition of writhing (P value < 0.001 in both cases). None of t he test samples showed antipyretic activity in rat model at a dose of 50 mg/kg body wt in comparable with standard ant ipyretic drug Paracetamol. On the other hand benzim idazole- 2-thiol reduced blood glucose level with respect to standard drug Glibenclamide having P value 0.00082 and 3- bromopropyl ammonium bromide lengthened the Na-phen obarbitone induced sleeping time having the P value 0.0009 which was statistically significant.